Double burden, ketimpangan gender, dan produktivitas kerja perempuan pemulung di Komunitas Pemulung Pasir Panjang Kota Kupang: A Double burden, gender inequality, and work productivity of women scavengers in the Pasir Panjang Scavenger Community, Kupang City - Medho, Yohana Fransiska; Tan, Petrus; Bidi, Maximianus Ardon; Niron, Eusabius Separera (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
Scavenging has been the object of scientific and academic research based on various scientific viewpoints worldwide. Still, the issue of the double burden that is experienced by women scavengers and its impact on gender inequality and women's productivity has received less attention. This research aims to explore further the effects of double burden or dual responsibility burdened by women scavengers in Komunitas Pemulung Pasir Panjang Kota Kupang, East Nusa Tenggara (NTT), to gender inequality and the productivity of women scavengers in that community. This research employed a qualitative approach including field observation and in-depth interviews. This research has found that the phenomena of double burden does not liberate women scavengers from the patriarchal chain that binds and restrains them, but instead makes them increasingly dependent on men in the economic and financial dimension of household life. In addition, they are caught in a dilemma between maximizing the option of working outside the home or taking care of their domestic work. As a consequence of the long-standing and strong internalization of a false awareness about women's natural duties, those women scavengers do not think of this as an injustice but rather an obligation that must be carried out properly and consistently.